2012
DOI: 10.4049/jimmunol.1103415
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of Cytokine Signaling Promote Fas-Induced Apoptosis through Downregulation of NF-κB and Mitochondrial Bfl-1 in Leukemic T Cells

Abstract: Suppressors of cytokine signaling (SOCS) are known as negative regulators of cytokine- and growth factor–induced signal transduction. Recently they have emerged as multifunctional proteins with regulatory roles in inflammation, autoimmunity, and cancer. We have recently reported that SOCS1 has antiapoptotic functions against the TNF-α– and the hydrogen peroxide–induced T cell apoptosis through the induction of thioredoxin, which protects protein tyrosine phosphatases and attenuates Jaks. In this study, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…pAkt expression was also significantly upregulated in SOCS3 stables. Further it has been shown that SOCS1 has antiapoptotic properties and SOCS3 is important for the survival of prostate cancer cells (24,25). In our studies we observed that SOCS3 overexpression diminished the H 2 O 2 induced caspase-3 cleavage and enhanced expression of the prosurvival molecule Bcl2.…”
Section: Figsupporting
confidence: 63%
“…pAkt expression was also significantly upregulated in SOCS3 stables. Further it has been shown that SOCS1 has antiapoptotic properties and SOCS3 is important for the survival of prostate cancer cells (24,25). In our studies we observed that SOCS3 overexpression diminished the H 2 O 2 induced caspase-3 cleavage and enhanced expression of the prosurvival molecule Bcl2.…”
Section: Figsupporting
confidence: 63%
“…Since NF‐κB p50 is produced as a proteolytic product of the pre‐form NF‐κB1 (p105), for qualitative purpose, the inhibitory effect of β‐eudesomol on NF‐κB (p50) expression was considered as the representative measure of NF‐κB1/p50 downregulation. Similar studies involving chemostress‐induced downregulation of NF‐κB (p65) protein have previously been employed to access the inhibitory effects of various compounds on NF‐κB expression in leukemic T and hepatic cancer cells . Taken together, the inhibitory effect of β‐eudesmol on the production of cytoprotective enzymes and stimulatory effect on the expression of key transcriptional factor proteins may be linked to the observed cytotoxicity of the compound on CL‐6 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, a downregulation of NFKB promotes Fas-induced apoptosis in T cells [36]. NFKB comprises a family of critical transcription factors involved in a variety of immunologic and/or inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%